Peran NGO Transnasional dalam Konservasi Penyu di Kabupaten Berau: Studi Dokumen Yayasan Penyu Indonesia - Vinna Faulina; Khoirul Amin; Mohammad Dziqie Aulia Al Farauqi (SENTRI: Jurnal Riset Ilmiah, 2026)
Sea turtle conservation represents a global environmental challenge that increasingly involves non-state actors, particularly transnational non-governmental organizations (NGOs). This study examines the role of transnational NGOs in sea turtle conservation efforts in Berau Regency, Indonesia, with a focus on cooperation patterns, funding mechanisms, and the transfer of global conservation norms to the local level. Employing a qualitative research design, the study utilizes a document-based approach by analyzing annual reports, cooperation documents, program descriptions, and official publications of the Indonesian Turtle Foundation (Yayasan Penyu Indonesia/YPI), which functions as the implementing partner of transnational NGOs. Data were analyzed through thematic procedures encompassing data reduction, data presentation, and conclusion drawing. The findings reveal that the role of transnational NGOs extends beyond financial assistance to include strengthening local institutional capacity, standardizing conservation practices in accordance with global norms, and fostering active participation among coastal communities. Notably, the study identifies a significant shift in community behavior, particularly among coastal residents who were previously involved in egg harvesting and have gradually transformed into active nest protectors and conservation volunteers as a result of NGO-led education, incentive schemes, and community-based conservation programs. The study further demonstrates that sea turtle conservation in Berau is implemented through a multi-actor governance framework involving NGOs, international donors, local governments, and community stakeholders, reflecting the dynamics of global environmental governance. Additionally, the research highlights the process of global norm diffusion, whereby international conservation values are translated into localized practices through education, advocacy, and community engagement. By situating sea turtle conservation within an international relations perspective, this study contributes to the literature by emphasizing the political and governance dimensions of environmental conservation and underscoring the strategic significance of transnational NGOs in shaping sustainable conservation outcomes at the local level.